2019
DOI: 10.3389/fneur.2019.00769
|View full text |Cite
|
Sign up to set email alerts
|

A Non-linear Association Between Total Small Vessel Disease Score and Hemorrhagic Transformation After Ischemic Stroke With Atrial Fibrillation and/or Rheumatic Heart Disease

Abstract: Background: Previous studies have investigated the association between a single marker of cerebral small vessel disease (SVD) and hemorrhagic transformation (HT). However, the effect of the total SVD burden on HT has not been evaluated yet. We aimed to investigate the association between the total SVD score and HT in ischemic stroke patients with atrial fibrillation (AF) and/or rheumatic heart disease (RHD). Methods: Ischemic stroke patients with AF and/or RHD admitted within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…In previous studies, the proportion of stroke patients with HT varied largely between 50.81% (Wei et al, 2019) and 5.9% (Valentino et al, 2017) in the literature. Difference in the time interval between stroke onset, in the modality of follow-up imaging and in the population of stroke patients included in the studies partially explains the discrepancies between the reported different rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the proportion of stroke patients with HT varied largely between 50.81% (Wei et al, 2019) and 5.9% (Valentino et al, 2017) in the literature. Difference in the time interval between stroke onset, in the modality of follow-up imaging and in the population of stroke patients included in the studies partially explains the discrepancies between the reported different rates.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the majority of strokes were classified as noncardioembolic. Conversely, another retrospective study of 207 patients presenting with acute stroke and AF and/or rheumatic heart disease evaluated with brain MRI or CT scan up to 7 days after admission supported a potential role for leukoaraiosis in predicting HT after acute ischemic stroke (Wei et al., 2019). Moreover, Bivard et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scanning sequences included SWI, fluid-attenuated inversion recovery (FLAIR) imaging, T1-weighted imaging, T2-weighted imaging, and diffusion-weighted imaging (DWI). Detailed MRI parameters have been described in our previous studies [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hemorrhagic transformation (HT) was defined as hemorrhage within the infarct territory or parenchyma hemorrhage outside the infarct lesion that was detected on follow-up CT or MRI during hospitalization, but not on head CT on admission [ 33 ]. As in our previous studies [ 31 , 32 , 34 ], we further divided HT into hemorrhagic infarction (HI), parenchymal hemorrhage (PH) based on the criteria of radiographic appearance [ 35 ], and symptomatic HT (sHT) on neurological symptoms [ 36 ]. Large hemispheric infarction was recorded when the infarct area was larger than 1/2 of the blood supply area of the middle cerebral artery (MCA) on FLAIR and/or DWI [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%